2015
DOI: 10.1021/jf505247d
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Identification and Expression of Starch and Sucrose Metabolism Genes in the Seeds of Chinese Chestnut (Castanea mollissima)

Abstract: The Chinese chestnut (Castanea mollissima) seed provides a rich source of carbohydrates as food and feed. However, little is known about starch biosynthesis in the seeds. The objectives of this study were to determine seed composition profiles and identify genes involved in starch and sucrose metabolism. Metabolite analysis showed that starch was the major component and rapidly accumulated during seed endosperm development. Amylopectin was approximately 3-fold of amylose content in chestnut starch. Illumina pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 52 publications
3
48
0
Order By: Relevance
“…Amylopectin accounts for almost 75% of total starch in ripening chestnut, and the remaining 25% was amylose [21]. In our study, the ratio of amylopectin to amylose increased significantly through chestnut cotyledon development.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…Amylopectin accounts for almost 75% of total starch in ripening chestnut, and the remaining 25% was amylose [21]. In our study, the ratio of amylopectin to amylose increased significantly through chestnut cotyledon development.…”
Section: Discussionsupporting
confidence: 51%
“…In Arabidopsis , SBE I did not expressed and its function was unknown, while SBE II had been classified into SBE 2.1 and SBE 2.2 [47]. Transcriptomic analysis of Chinese chestnut revealed two SBE unigenes; however, the isoforms and sequences of SBE were not defined [21]. In this study, we firstly identified and characterized two chestnut SBE isoforms involved in starch metabolism in chestnut by SDS-PAGE and MS analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Wang et al [21] conducted a detailed transcriptional sequencing analysis of two orange varieties at different fruit development stages to elucidate the underlying regulatory mechanism of sucrose and citrate accumulation in the ripening of the fruits, especially during the fruit delayed-harvest stage. Zhang et al [23] explored the key regulatory factors involved in starch and sucrose metabolism in Castanea mollissima via transcriptome sequencing of seeds at various developmental stages. However, only a single study has reported transcriptome profiles obtained using a mixture of the leaves and inflorescences of Z. armatum to isolate the viruses associated with flower yellowing disease in recent years [24].…”
Section: Introductionmentioning
confidence: 99%